PENGEMBANGAN INSTRUMEN MENGGUNAKAN SPINNER QUESTION UNTUK MEMFASILITASI MINAT BELAJAR PESERTA DIDIK SMP PADA MATERI TATA SURYA - Labibah, Hana; Vitasari, Mudmainah; Rohimah, Ratu Bai (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
Students' interest in learning is one of the important factors in the success of science learning, especially in the Solar System material which is abstract and requires active student involvement. However, the instruments used in schools are generally still conventional, so they are less capable of facilitating students' interest in learning. This study aims to develop and test the feasibility of the Spinner Question instrument in facilitating middle school students' interest in learning about the Solar System. This study uses a research method called Research and Development (R&D) with the Borg and Gall model modified into six stages, namely research and information collection, planning, developing a preliminary form of the product, preliminary field testing, main product revision, and main field testing. The research subjects involved seventh-grade students at SMP Negeri 1 Ciomas, as well as validation by content experts, media experts, instrument experts, and practitioners. The developed instrument consisted of a test instrument containing essay questions. Instrument validation was conducted theoretically through assessments by content experts, media experts, instrument experts, and practitioners, as well as empirically through item analysis including validity test, reliability, difficulty level, and discriminating power. The results of the study showed that the instrument using Spinner Question obtained a validity percentage of 90.35%, categorized as "very valid." In addition, the students' response to the use of the instrument with Spinner Question reached 81.7%, categorized as "very good." These results indicate that the instrument using Spinner Question is feasible to use and can facilitate students' interest in learning the Solar System material. ABSTRAK Minat belajar peserta didik merupakan salah satu faktor penting dalan keberhasilan pembelajaran IPA, khususnya pada materi Tata Surya yang bersifat abstarak dan membutuhkan keterlibatan aktif peserta didik. Tetapi instrument yang digunakan di sekolah umumnya masih bersifat konvensional sehingga kurang mampu memfasilitasi minat belajar peserta didik. Penelitian ini bertujuan untuk mengembangkan dan menguji kelayakan instrument Spinner Question dalam memfasilitasi minat belajar peserta didik SMP pada materi Tata Surya. Penelitian ini menggunakan metode penelitian yang digunakan Adalah Research and Development (R&D) dengan model Borg and Gall yang dimodifikasi menjadi enam tahap, yaitu research and information collection, planning, develop preliminary form of product, preliminary field testing, main product revision, dan main field testing. Subjek penelitian melibatkan peserta didik kelas VII SMP Negeri 1 Ciomas serta validasi oleh ahli materi, ahli media, ahli instrument dan ahli praktisi. Instrumen yang dikembangkan berupa instrumen tes berisi soal-soal esai. Validasi instrumen dilakukan secara teoritis melalui penilaian ahli materi, ahli media, ahli instrumen, dan praktisi, serta secara empiris melalui analisis butir soal yang meliputi uji validitas, reliabilitas, tingkat kesukaran, dan daya beda. Hasil penelitian menunjukkan bahwa instrument menggunakan Spinner Question memperoleh pesersentase kevalidan 90,35% dengan kategori “sangat valid”. Selain itu respon peserta didik terhadap penggunaan instrumen menggunakan Spinner Question mencapai 81,7% dengan kategori “sangat baik”. Hasil ini menunjukkan bahwa instrumen menggunakan Spinner Question layak digunakan dan mampu memfasilitasi minat belajar peserta didik pada materi Tata Surya.